Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/diagnostics11020149
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metabolic Signatures of Prostate Cancer Revealed by 1H-NMR Metabolomics of Urine

Abstract: Prostate cancer (PC) is one of the most common male cancers worldwide. Until now, there is no consensus about using urinary metabolomic profiling as novel biomarkers to identify PC. In this study, urine samples from 50 PC patients and 50 non-cancerous individuals (control group) were collected. Based on 1H nuclear magnetic resonance (1H-NMR) analysis, 20 metabolites were identified. Subsequently, principal component analysis (PCA), partial least squares-differential analysis (PLS-DA) and ortho-PLS-DA (OPLS-DA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Various studies have shown that urine NMR metabolomics has potential as a screening tool for accurate diagnosis [ 26 , 27 , 28 ]. Since, to the best of our knowledge, no investigation has been performed so far on the urine metabolome of BAV subjects, in the present study we applied urine-based metabolomics for a comparative analysis of the metabolic profile of adult asymptomatic subjects with BAV ( n = 20) and healthy controls ( n = 24).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that urine NMR metabolomics has potential as a screening tool for accurate diagnosis [ 26 , 27 , 28 ]. Since, to the best of our knowledge, no investigation has been performed so far on the urine metabolome of BAV subjects, in the present study we applied urine-based metabolomics for a comparative analysis of the metabolic profile of adult asymptomatic subjects with BAV ( n = 20) and healthy controls ( n = 24).…”
Section: Discussionmentioning
confidence: 99%
“…Before the data analysis, we checked the data integrity. The normalization of the soil variables was carried out using the statistical package in R software version 4.0.2 (R Core Team, Austria) [ 44 ] based on the geometric mean, and a generalized logarithmic transformation using “glog” function in R was performed to make the variables comparable among themselves due to differences in the units to measure them [ 45 , 46 ]. Figure 8 shows the general scheme of the data analysis procedures followed in this work.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the Cao et al study investigating sarcosine levels in urine supernatant and sediment, the creatine-and alaninenormalized sarcosine levels were statistically higher in PCa patients than in abnormal prostate without cancer patients or healthy patients, from both sample source and normalization protein [123]. A very recent study using a PCa urine-based 1 H-NMR revealed that guanidinoacetate, phenylacetylglycine, and glycine were significantly increased while L-lactate and L-alanine were substantially decreased [124]. In the 20 metabolites identified, sarcosine was not even a player in PCa after employing principal component analysis (PCA), partial least squares-differential analysis (PLS-DA), ortho-PLS-DA (OPLS-DA), and the Wilcoxon test.…”
Section: Why Focus On Metabolomics For Pca Cancer Research?mentioning
confidence: 96%